Health, performance and conduct concerns among older doctors: A retrospective cohort study of notifications received by medical regulators in Australia. Issue 2 (April 2018) - Thomas, Laura A; Milligan, Eleanor; Tibble, Holly; Too, Lay S; Studdert, David M; Spittal, Matthew J; Bismark, Marie M
Objectives: To determine whether 'older doctors' (aged over 65) are at higher risk of notifications to the medical regulator than 'younger doctors' (aged 36–60 years) regarding their health, performance and/or conduct. Design: Retrospective cohort study. Setting: National dataset of 12, 878 notifications lodged with medical regulators in Australia between 1 January 2011 and 31 December 2014. Participants: All registered doctors in Australia aged 36–60 and >65 years during the study period. Main outcome measures: Incidence rates of notifications and incidence rate ratios of notifications (older versus younger doctors). Results: Older doctors had higher notification rates (90.9 compared with 66.6 per 1000 practitioner years, p < 0.001). Sex-adjusted incidence rate ratios showed that older doctors had a higher risk of notifications relating to physical illness or cognitive decline (incidence rate ratio = 15.54), inadequate record keeping (incidence rate ratio = 1.98), unlawful use or supply of medications (incidence rate ratio = 2.26), substandard certificates/reports (incidence rate ratio = 2.02), inappropriate prescribing (incidence rate ratio = 1.99), disruptive behaviours (incidence rate ratio = 1.37) and substandard treatment (incidence rate ratio = 1.24). Older doctors had lower notification rates relating to mental illness and substance misuse (incidence rate ratio = 0.58) and for performance issues relating to problems with procedures (incidence rate ratio = 0.61). Conclusions: Older doctors were at higher risk for notifications relating to physical or cognitive impairment, records and reports, prescribing or supply of medicines, disruptive behaviour and treatment. They were at lower risk for notifications about mental illness or substance misuse. Incorporating knowledge of these patterns into regulatory practices, workplace adjustments and continuing education/assessment could enhance patient care.